Screening and detection of antibiotic residues on broiler meat based on trade system variations, seasonal differences, and the impact on final consumer safety in Romania - Pogurschi, Elena Narcisa; Grigore, Daniela-Mihaela; Ianitchi, Daniela; Bahaciu, Gratziela; Popa, Dana Catalina; Dragomir, Nela; Pet, Ioan (Frontiers in Sustainable Food Systems, 2023)
Introduction One key factor contributing to microbial resistance is the deliberate and inappropriate use of antibiotics in human and animal health management. Recent studies point out various ways to tackle this controversy to mitigate the unnatural rapid evolution of pathogenic bacteria. Chicken meat remains at the top of Romanian consumers' preferences, being the most consumed type of meat, desired for its nutritional and dietetic attributes. Methods This research was conducted in 2022, aiming to evaluate the antibiotic residues (quinolones, aminoglycosides, tetracycline, and sulfonamides) in broiler chicken meat with various trade strategies [retail market (RM), n = 40, traditional market (TM), n = 185, and door-to-door vendors (DTD), n = 121] during two seasonal periods, spring (March–April) and summer (July–September). An efficient and precise protocol was employed for determining the meat organoleptic attributes, qualitative screening, and quantitative assay antibiotic of six antibiotics (enrofloxacin, marbofloxacin, streptomycin, oxytetracycline, doxycycline, and sulfamethoxazole), consumers' antibiotic exposure (estimated daily intake), and potential risk assessment (hazard quotient). Results The antibiotic quality assessment revealed an overall antibiotic residue presence in groups TM (75%) and DTD (82%), while no antibiotic residues were detected in the RM group. Our results show that 32% (n = 110) of the total chicken meat samples were free of antibiotic residues, 4.5% (n = 16) contained antibiotic residues belonging to one class of antibiotics, 40% (n = 139) had two antibiotics groups, 22% (n = 77) had three antibiotics groups, and 1.5% of the chicken meat samples presented four groups of antibiotics. Discussion During the spring season, the enrofloxacin antibiotic residue present in the meat samples was higher, showing an 84% presence in TM meat samples group when compared with the DTD meat sampled group (75%). The analysis data processing showed a strong correlation between the antibiotic residue's meat samples origin (trade market and door-to-door traded meat antibiotic residue variations) and seasonal variations. As a result of the hazard quotient assay, the meat antibiotic residue levels had subunit values, indicating the meat quality was proper for consumption. It is mandatory to strengthen the level of knowledge by continuously monitoring and providing updated information to each group of farmers to increase their understanding of and adherence to the proper handling of antibiotics when growing chickens. Regarding the use of prohibited growth-promoting antibiotics in chicken-rearing systems, local authorities should increase the guard level, at antibiotic supplier and end user levels.